2011
DOI: 10.1037/a0022769
|View full text |Cite
|
Sign up to set email alerts
|

Children conceived by gamete donation: Psychological adjustment and mother-child relationships at age 7.

Abstract: An increasing number of babies are being born using donated sperm, where the child lacks a genetic link to the father, or donated eggs, where the child lacks a genetic link to the mother. This study examined the impact of telling children about their donor conception on mother-child relationships and children's psychological adjustment. Assessments of maternal positivity, maternal negativity, mother-child interaction and child adjustment were administered to 32 egg donation, 36 donor insemination and 54 natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 57 publications
3
71
1
3
Order By: Relevance
“…One wonders why they have done the study in the first place. A similar reasoning pattern can be found in Golombok et al (2011): 'No differences between family types were found for maternal negativity, showing that conflict and hostility between mothers and children is no higher in nondisclosing than disclosing gamete donation families or natural conception families. In addition, the children were found to be functioning well.'…”
Section: Findings and Conclusion/ Recommendationssupporting
confidence: 69%
“…One wonders why they have done the study in the first place. A similar reasoning pattern can be found in Golombok et al (2011): 'No differences between family types were found for maternal negativity, showing that conflict and hostility between mothers and children is no higher in nondisclosing than disclosing gamete donation families or natural conception families. In addition, the children were found to be functioning well.'…”
Section: Findings and Conclusion/ Recommendationssupporting
confidence: 69%
“…Phase 1 was conducted when the children were 1 year old , Phase 2 was conducted at Age 2 (Golombok, Jadva, Lycett, Murray, & MacCallum, 2005), Phase 3 was conducted at Age 3 , Phase 4 was conducted at Age 7 Golombok, Readings, Blake, Casey, Mellish, et al, 2011) and Phase 5 was conducted at Age 10 (Golombok, Blake, Casey, Roman, & Jadva, 2013). In the preschool years, the differences identified between family types pointed to more positive parent-child relationships in families created by gamete donation than in the comparison group of natural conception families, with no differences in the quality of family relationships according to whether the children lacked a genetic connection to the father (in the case of donor insemination) or the mother (in the case of egg donation) Golombok et al, 2005;.…”
Section: Family Functioning In Disclosing Familiesmentioning
confidence: 99%
“…In contrast to the more positive outcomes for the donor conception families in the preschool years, greater difficulties emerged at Age 7 Golombok, Readings, Blake, Casey, Mellish, et al, 2011), the age by which children show an understanding of biological inheritance (Gregg, Solomon, Johnson, Zaitchik, & Carey, 1996;Williams & Smith, 2010) and the meaning and implications of the absence of a biological connection to parents (Brodzinsky & Pinderhughes, 2002). The gamete (egg and sperm) -donation mothers who had kept their children's origins secret showed higher levels of emotional distress than did those who had been open with their children about their origins.…”
Section: Family Functioning In Disclosing Familiesmentioning
confidence: 99%
“…This is consistent with studies showing that children who do not know about their donor conception are doing as well as non-donorconceived children in terms of general emotional, social and behavioural development 17,35,36 . Likewise, other studies found no differences in the children's psychological well-being and the parent-child relationships between the disclosing and the non-disclosing families 14,37,38 . Our survey disclosed the attitudes of future parents on various aspects of "disclosure".…”
Section: Discussionmentioning
confidence: 88%